HILOS DE TEATRO: LA PUESTA EN ESCENA DEL PALACIO DE LOS SOVIETS DE LE CORBUSIER, 1931 / Strands of theatre: Le Corbusier’s staging of the Palace of the Soviets, 1931 - González Cubero, Josefina (Proyecto, Progreso, Arquitectura, 2012)
RESUMEN El proyecto para el concurso del Palacio de los Soviets en Moscú (1931) de Le Corbusier plantea otra posible y más fragmentaria clave de interpretación que, aunque en principio sea más marginal, merece ser mencionada: la relación con el teatro, con la renovación de la escena europea y con la experimentación soviética, porque Le Corbusier es consciente de que la arquitectura no consiste sólo en la cualidad del edificio, es también una puesta en escena, una dramaturgia. Escenógrafos como Appia, con la luz, o directores de escena como Max Reinhardt, con el espectáculo de masas, y Vsevelod Meyerhold, con el teatro japonés del Kabuki, van penetrando en el sentir de un Le Corbusier que deja la impronta teatral en la puesta en escena de la megaestructura moscovita. SUMMARY Le Corbusier’s design submitted to the public competition for the Palace of the Soviets in Moscow (1931) may have an additional interpretation which, although less researched and in principal more marginal, is noteworthy. And that is the relationship between theatre and the resetting of the stage in Europe and Soviet experimentation. Le Corbusier was aware that architecture goes beyond the building itself and is also a sort of staging or dramaturgy. Set designers such as Appia, through the use of light, or stage directors like Max Reinhardt, through the use of performance for the masses, and Vsevelod Meyerhold, through Japonese Kabuki theatre, gradually permeated the sensibility of Le Corbusier who left staging as a mark in his design for the Moscow megastructure.